The efficiency of grid-tied PV systems on small farms in Latvia - Normunds Stanka; Aivars Aboltins (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2021)
Photovoltaic (PV) systems are becoming more and more popular around the world, and Latvia is not an exception. This is mainly due to the increased efficiency and reduction in price of PV modules. However, Latvia still ranks below most European Union countries in the use of PV modules for electricity production. A significant problem for many farms and households in Latvia which use PV modules, is the lack of storage for the produced electricity. As a result, large amounts of electricity are sold for a relatively low price and while being bought from the main grid for a relatively high price. The aim of the study is to determine and compare the electricity consumption and PV systems producing electricity each month on the Jasmini Farm during 2020. The study shows that during the year, only 25.4% of all the electricity used on the Jasmini Farm was from PV modules, but the rest of the electricity was bought from the main grid. Furthermore, from all the electricity which PV modules produced in 2020, only 29.5% was used on the farm, while the rest was sold to the main grid.